No meat athlete : a plant-based nutrition and training guide for athletes at any level - Frazier, Matt; Ruscigno, Matthew
"The plant-based guide you need to perform at your very best, no matter where you are on your fitness journey. Combining proven training plans, easy yet innovative recipes, and motivational stories into a unique fitness guide, healthy-living cookbook, and nutrition primer, [this book] is perfect for all athletes, from beginner to elite, who want to enjoy the health benefits of a meatless lifestyle. Veganism, already a top food trend and diet, is taking off in the sports world. The lifestyle has been adopted by Olympians, body builders, and boxers, as well as top athletes in the NBA and NFL. Hollywood is on board, too. James Cameron (director of Avatar and Titanic) has produced a film on the topic called The Gamechangers, which follows vegan athletes, including Arnold Schwarzenegger, U.S. Olympian Kendrick James Farris, and surfer Tia Blanco. ...Author, blogger, and hundred-mile ultramarathoner Matt Frazier will show you the many benefits to embracing a plant-based athletic lifestyle...In this revised and updated edition, you'll also find new recipes, advice, and an all-new 12-week strength training plan designed to improve your overall fitness. Section I of the book provides practical advice for transitioning to a plant-based lifestyle, while ensuring you are getting all the nutrition you need. In Section II, Matt delivers training manuals of his own design for runners of all ability levels and ambitions, including tips for creating healthy habits, improving performance, and avoiding injuries. ...Your road map to top-notch performance, the plant-based way!"--provided by Amazon.com.
Previous edition: 2013.
"Includes more than 60 recipes!"
Keywords: Runners (Sports); Athletes; Physical fitness; Vegan cooking; Veganism; Running